EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN BERBASIS PROYEK DALAM MENINGKATKAN KETERAMPILAN SOSIAL SISWA SEKOLAH DASAR - Juliawan, I Wayan; Susanta, I Wayan; Mulyawan, I Nyoman Rajeg; Suastini, Ni Wayan; Badriyah, Rr Dwi Umi; Suharditha, Kadek; Datuti, Sri (Jurnal Ilmiah Pendidikan Citra Bakti, 2025)
This study aimed to describe the application of project-based learning model to improve the social skills of class V students at SDN 1 Kediri and class V students at SDN 5 Kediri District after participating in project-based learning. This research is a classroom action research using project-based learning. The research subjects were students in class V at SDN 1 Kediri and students in class V at SDN 5 Kediri, Tabanan Regency, totaling 60 students. Students' social skills are measured based on the increase in the percentage of students' social skills during the learning process. The research instrument used was the social skills observation sheet. Based on the study's results, it can be concluded that project-based learning can improve the social skills of class V students at SDN 1 Kediri and class V students at SDN 5 Kediri Tabanan Regency in learning science. Students' social skills improved from 67.35 before treatment to 88.24 after treatment. Based on these results indicate that project-based learning is effective in enhancing students' social skills